THE ROLE OF “CAS CIS CUS” FAIRYTALE IN ANTI CORRUPTION EDUCATION AT AL ISLAM KINDERGARTEN 5 SURAKARTA - Sidik Nuryanto; M Fadlillah (Universitas Muhammadiyah Ponorogo, 2018)
Corruption is a big problem that exists in this country. One of preventing thing that is done through Anti-corruption education since early childhood. The title of this research is the role of “CAS CIS CUS” Fairytale in Anti-Corruption education at AL ISLAM Kindergarten 5 Surakarta. The study case of qualitative method research with subjects 2 teachers and 31 students and their parents. The collection of data through observation, interview, and documentation. The validity of data by testing the degree of trust, diversion, dependent and certainty. Data analysis with interactive model that consists of data reduction, data presentation, and conclusion. The result of discussion includes the implementation of Anti corruption education with CAS CIS CUS fairytale divides into three phases of fairytale; They are”CAS (Cipta Aksi Super), “CIS (Cipta Inspirasi Super), and“CUS” (Cipta Usulan Super). An anti-Corruption value includes honesty, hard work, discipline and responsibility. The supporting factor is giving fairytale program and enhancement of teacher’s competence, meanwhile the problem comes from parents.